Proceedings of the Proceedings of the 1st International Conference on Applied Social Sciences, Business, and Humanity, ICo-ASCN 2020
DOI: 10.4108/eai.1-11-2019.2293991
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Formal Tax Education in Secondary School: A Survey on Malaysian Public’s Perception

Abstract: Taxpayers' compliance level of a country reflects its citizens' knowledge about taxation system and, their connection and trust towards the government. However, low compliance level of individuals' and companies has raised the question of the adequacy and effectiveness of citizen tax knowledge in Malaysia and whether tax education is warranted. This study is an overview on the Malaysian public's perception towards introducing formal tax education in secondary schools. First, it looks at current taxpayer's tax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…As a result, non-accounting students should be taught about taxes. An early and formal tax education will help future taxpayers understand the taxation system and their tax responsibilities [15,20]. The authors of [3] found a significant difference in tax knowledge between Indonesian students who received tax education and those who did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, non-accounting students should be taught about taxes. An early and formal tax education will help future taxpayers understand the taxation system and their tax responsibilities [15,20]. The authors of [3] found a significant difference in tax knowledge between Indonesian students who received tax education and those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…This annual program seeks to provide a variety of tax-related educational activities to students at all levels of education, including elementary, middle, high, and university. In Malaysia, the Inland Revenue Board of Malaysia (IRBM) has launched several informal education programs for schoolchildren, including tax camps, junior tax officers at Kidzania, speech contests, quizzes, and trips to IRBM offices [15]. It is undeniably beneficial for pupils to understand taxes at a young age, since they will be paying taxes in the future.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Ministry of finance of the Republic of Indonesia in 2018, an increase in tax awareness needs to be done from an early age and should be inculcated in the educational environment from elementary to tertiary level. Tax education must be started early on, through the understanding of tax knowledge on high school students, to be able to increase tax awareness and tax attitudes in the future [10]- [13], this manner also could be applied to school children as a potential taxpayer who has an impact on educated their ability to pay taxes in the future [12], [14].…”
Section: Introductionmentioning
confidence: 99%